Exploring the Role of Scrap Markets in Advancing the Circular Economy in Nepal: A Field-Based Study - Pant, Keshab Raj; Chataut, Ram Kumar (NPRC Journal of Multidisciplinary Research, 2025)
Scrap markets have become an integral component of sustainable waste management and circular economy (CE). Through the descriptive field-based research in four urban municipalities of Kailali District, Nepal, this study explores the role of scrap markets in advancing circular economy (CE). Surveys with 54 scrap firm owners shows that the informal sector contributes over 92% of traded scrap, where cycle hawkers alone accounting for 86.47%.  Small, unregistered firms buy scrap from informal collectors and sell to larger dealers for recycling and export scrap to industries. The market monthly trades an average of 2,223.54 tons with a net profitability of 6.13%. Glass bottles (53.51%), metal scrap (18.99%), and paper scrap (18.80%) dominate the market, with paper scrap among the most profitable items except Burnt engine oil. Scrap markets support environmental sustainability by reducing landfill pressure for municipal waste. Raising recycling awareness on communities, formalizing informal scrap collectors and infrastructural development for micro-segregation of municipal waste can enhances overall circular economy outcomes.